2021
DOI: 10.1038/s41396-021-00894-1
|View full text |Cite
|
Sign up to set email alerts
|

Increasing flavonoid concentrations in root exudates enhance associations between arbuscular mycorrhizal fungi and an invasive plant

Abstract: Many invasive plants have enhanced mutualistic arbuscular mycorrhizal (AM) fungal associations, however, mechanisms underlying differences in AM fungal associations between introduced and native populations of invasive plants have not been explored. Here we test the hypothesis that variation in root exudate chemicals in invasive populations affects AM fungal colonization and then impacts plant performance. We examined flavonoids (quercetin and quercitrin) in root exudates of native and introduced populations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 69 publications
1
90
0
1
Order By: Relevance
“…Recent studies have shown that content of quercetin is high in root exudates of invasive plants Triadica sebifera (L.) Small. The substance, as a part of exudates, is key in signaling for the interaction of plants with mycorrhizal fungi and soil microorganisms in general [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that content of quercetin is high in root exudates of invasive plants Triadica sebifera (L.) Small. The substance, as a part of exudates, is key in signaling for the interaction of plants with mycorrhizal fungi and soil microorganisms in general [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Li et al (2020) found that invasive populations of C. odorata produced greater quantities of phenolic compounds; some of these phenolic compounds confer stronger defence and others may suppress native species (Table 1). Recently, Tian et al (2021) recorded more quercetin, a flavonoid, in root exudates of 60-or 90-day old Triadica sebifera plants from the non-native (USA) than from the native (China) range. Quercetin causes higher colonization by arbuscular mycorrhizal fungi of invasive populations of T. sebifera than of its native populations (Fig.…”
Section: Accepted Articlementioning
confidence: 99%
“…Root exudates contain quercetin Root exudates facilitate greater mycorrhizal colonisation of T. sebifera in the non-native range than in the native range (Tian et al, 2021) a Native vs non-native ranges.…”
Section: Novel Chemicals Introduced By Nismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Medicago truncatula mutants unable to establish AMF symbiosis grown in field soil under greenhouse conditions had reduced microbial abundance in the rhizosphere, suggesting a role for conserved symbiotic pathways in rhizosphere enrichment processes (Wang et al, 2021). Although flavonoids are present across the plant kingdom (e.g., Lapcik et al, 2006;Tian et al, 2021), accumulated evidence suggests they are particularly prevalent among legumes (Veitch, 2007;Jasiński et al, 2009) and their importance in multiple initiation and regulatory functions pertaining to intracellular symbiosis cannot be understated. While there is limited research on differences in flavonoid profiles among legumes and non-legumes, Weston and Mathesius (2013) note that species-specific differences in root flavonoid exudation could be responsible for various rootmicrobe interactions.…”
Section: Legume-microbial Signaling In the Rhizospherementioning
confidence: 99%